The impending summit meeting of the ten - Günther Jantzen (Intereconomics, 1972)
A summit meeting of the European Ten is planned for the autumn, and it is to take place. Its main subject will be foreign policy. True, scant information was given out on the contents of the talks held between Presldent Pompidou and Federal Chancellor Brandt in Bonn early in July, but even the meagre official statements issued about them gave the impression that the two men are still of the opinion that the subject of a common foreign policy is of importance for their two countries.
Keywords: 330; Development Policy